Peran Lembaga Pemberdayaan Masyarakat Desa (LPMD) Dan Pemerintah Desa Dalam Perencanaan Pembangunan Desa (Studi pada Desa Kemantren Kecamatan Jabung Kabupaten Malang) - Purwaningsih, Rizki (Jurnal Administrasi Publik, 2015)
Abstract: Role of Village People Empowerment Agency (LPMD) and Village Government within the Planning for Village Development. (Studies in Rural District Jabung Kemantren Malang). Rural development can not be separated from the name of planning. The purpose of planning itself is to improve people's lives. As for planning to run in accordance with the needs and aspirations of the community it is necessary to optimize the role LPMD and Village Government in development planning. The focus of the research is to find out what the role of the Institute of Rural Community Empowerment (LPMD) and village governments in rural development planning. Keywords: Role, planning for village development Abstrak: Peran Lembaga Pemberdayaan Masyarakat Desa (LPMD) dan Pemerintah Desa dalam Perencanaan Pembangunan Desa (Studi Pada Desa Kemantren Kecamatan Jabung Kabupaten Malang). Perencanaan pembangunan desa bagian dari peran aparat pemerintah desa dan peran lembaga pemberdayaan. Tujuan dari peran aparat desa dan lembaga desa adalah meningkatkan perekonomian masyarakat. Kata kunci: peran, perencanaan pembangunan desa